PENGARUH TATA KELOLA PEMBAYARAN PAJAK ONLINE TERHADAP KEPATUHAN WAJIB PAJAK DAN PENCAPAIAN TARGET PENERIMAAN PAJAK HOTEL DI KOTA BOGOR - Abidin, Topan Zenal; Iskandar, Abubakar; Sudarsa, Agus Suarman (Administratie: Jurnal Administrasi Publik, 2022)
The purpose of this research to explain the governance of online tax payments at the Bogor City Regional Revenue Agency and determine whether there is an influence of online tax payment governance on hotel taxpayer compliance and the achievement of hotel tax revenue targets at the Bogor City Regional Revenue Agency. This research is an ex-post facto research using quantitative approach and functional correlation method. The data collection techniques used are questionnaires, and documentation studies. The data analysis technique uses descriptive analysis and simple linear regression. Based on the results of the analysis, it shows that: 1) the governance of hotel online tax payments carried out by BAPENDA of Bogor City is included in the good category with an average value of 4.14; 2) the governance of online tax payments that has been implemented by BAPENDA of Bogor City has a positive influence on the compliance of hotel taxpayers in Bogor City; 3) the governance of online tax payments that has been implemented by BAPENDA of Bogor City has a positive influence on the hotel tax revenue target in Bogor City.